Recent Advances in the Valorization of Biodiesel By-Product Glycerol to Solketal - Supongsenla Ao; Samuel Lalthazuala Rokhum (Journal of Chemistry)
The exponential rise of the biodiesel production has resulted in a considerable amount of glycerol as a by-product, which must be valorized to ensure the sector’s long-term viability. As a result, cost-effective glycerol conversions for significant value-added chemicals are essential for the biodiesel production in the long run. Solketal, a glycerol by-product, is obtained as a potential fuel additive in the biodiesel industry. Recently, several heterogeneous acid-catalysts stand out as a promising catalyst for solketal production where biomass-based catalyst gained attraction owing to their biodegradability, eco-friendly, and abundant availability. Furthermore, magnetic nanoparticles-derived catalysts along with sulfonated functionalized catalyzed, zeolites, resins, enzymatic, etc. have proved their efficiency in solketal production. In this review, a wider study on the recent advances of the catalysts has been discussed along with their preparation, various reaction parameters, its application, and efficiency for biodiesel industry. This study opens up incredible prospects for us to use renewable energy sources, which will benefit the industry, the environment, and the economy.